Spatial analysis software testing tool based on object-oriented techniques - Santra, Arupratan; Murali Krishna, I. V. (Geocarto international, 2008)
Object-oriented (OO) programming and system design have become the scalable methodology for large-scale enterprise and technology system designs. Spatial and geographic information system (GIS)-based systems are not exempt from this trend and have widely adopted object-oriented methodology. Testing strategies for systems developed with OO technologies need to be carefully evaluated. Specific features of OO technologies such as information hiding and close tying of data structures with class structures and the natural peculiarities of the spatial data require revisiting of test strategies for spatial applications built on OO technology. This article focuses on object-oriented testing trends and the development of associated tools in the GIS industry.